2019
DOI: 10.1101/2019.12.17.875880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholinergic circuit genes in the healthy brain are differentially expressed in regions that exhibit gray matter loss in Parkinson’s disease

Abstract: Structural covariance networks are able to identify functionally organized brain regions by gray matter volume covariance. In Parkinson’s disease, the posterior cingulate network and anterior cingulate network showed decreased gray matter and therefore we examined the underlying molecular processes of these anatomical networks in the healthy brain. Whole brain transcriptomics from post-mortem samples from healthy adults, revealed upregulation of genes associated with serotonin, GPCR, GABA, glutamate, and RAS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In addition, prior work from our group showed up-weighting of genes related to synaptic signalling and chemical synaptic transmission in regions showing loss of connectivity in Parkinson's patients at risk of dementia (Zarkali et al, 2020) as well as in regions with increased cortical iron deposition in PD (Thomas et al, 2021). In this way, regional variation in expression of genes relating to synaptic transmission is emerging as a common factor from studies, including by Keo et al (2021), using varying technologies and acquiring imaging data from different PD cohorts, suggesting that it is likely to be of significance in neurodegeneration in PD. Interestingly, Keo et al (2021) found enrichment of the differentially expressed genes in cholinergic cell markers.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…In addition, prior work from our group showed up-weighting of genes related to synaptic signalling and chemical synaptic transmission in regions showing loss of connectivity in Parkinson's patients at risk of dementia (Zarkali et al, 2020) as well as in regions with increased cortical iron deposition in PD (Thomas et al, 2021). In this way, regional variation in expression of genes relating to synaptic transmission is emerging as a common factor from studies, including by Keo et al (2021), using varying technologies and acquiring imaging data from different PD cohorts, suggesting that it is likely to be of significance in neurodegeneration in PD. Interestingly, Keo et al (2021) found enrichment of the differentially expressed genes in cholinergic cell markers.…”
mentioning
confidence: 85%
“…To investigate the biological processes and cell types that may be driving selective vulnerability of the cingulate cortex in PD, Keo et al (2021) (de Schipper et al, 2017). These networks are replicable and at least partly explained by patterns of regional gene expression (Alexander-Bloch et al, 2013;Romero-Garcia et al, 2018), although their neurobiological basis is not fully understood.…”
mentioning
confidence: 99%
See 3 more Smart Citations